Factors Affecting Relapse and Remission in Behcet's Uveitis Treated with Interferon Alpha2a - ÇELİKER ATABERK, HANDE; DİRESKENELİ, RAFİ HANER (MARY ANN LIEBERT, INC, 2019)
Purpose: To investigate factors affecting relapse and remission in patients with Behcet uveitis (BU) in the context of using the interferon alpha2a (IFN alpha 2a) therapy. Methods: Clinical records were reviewed of 32 patients (totaling 54 eyes) presenting with severe BU who had been treated with IFN alpha 2a therapy. Factors influencing relapsing-remitting course of BU during IFN alpha 2a therapy and after the cessation of the agent were evaluated. Possible affecting factors of recurrence were age, gender, duration of the Behcet disease, time elapsed before starting the drug, number of relapses before the starting of IFN alpha 2a, laterality, and presence of panuveitis. Results: Thirty patients (93.7%) responded to IFN alpha 2a therapy. Annual attack rate before and after IFN alpha 2a treatment was determined to be 4.03 +/- 3.19 (attack per year) and 0.58 +/- 1.07, respectively (P<0.001). In univariable statistical evaluation, women tended to have a lower relapse risk than men. Multivariable analyses showed that age was the major factor determining relapse rate, while the effect of gender was not statistically significant (P=0.196). The other probable influencing factors were not found to be statistically significant (P>0.05). Increase in visual acuity observed during last examination compared to initial examination was determined to be statistically significant (P=0.018). Conclusions: Even if the female gender was evaluated as a good prognostic factor in univariable analyses, it was not assessed as an effective prognostic factor in multivariable analyses. Being aged may be regarded a good prognostic factor on the relapsing-remitting course of patients with BU who were treated with IFN alpha 2a therapy.
Keywords: Behcet disease; Behcet uveitis; IFN alpha 2a; interferons; relapse; uveitis; LONG-TERM EFFICACY; PROGNOSTIC-FACTORS; VISUAL PROGNOSIS; DISEASE; THERAPY; SAFETY; INFLIXIMAB; INVOLVEMENT; MANAGEMENT